Duodenal trauma. (April 2017) - Johnston, Luke R; Wind, Gary; Bradley, Matthew J
Duodenal trauma represents a unique challenge to the surgeon due to its relative rarity, anatomic location, and often the difficulty in diagnosing and managing these injuries. Despite these challenges, significant advances have been made over the previous century, and mortality has fallen to as low as 17%. The CT scan is the primary modality for diagnosis in the blunt trauma patient, and thorough surgical exploration at laparotomy is the mainstay for penetrating injuries. Management is guided by the grade of injury, with low-grade hematomas managed by observation, intermediate grade injuries by primary repair, and high-grade injuries with a damage control surgery approach. While pyloric exclusion remains the most common technique to augment primary repair in intermediate and higher grade injuries, the utility of this procedure has come into question in current literature, and an overall 'less-is-more' surgical approach has been advocated in recent publications. Complications following duodenal trauma are common and include fistulae, duodenal obstruction, and infectious complications. However, the overall morbidity and mortality have improved with these injuries. Future investigation is needed to determine the optimal management approach for these challenging patients.